Electron paramagnetic resonance and optical investigations of defect centres in diamond - Du Preez, L (University of the Witwatersrand, Johannesburg, 1965)
A survey of the optical and electron paramagnetic resonance (E.F.R.) absorption in a large number of diamonds from all major sources of production has revealed that perfect diamond is virtually non-existent. One or more of eleven different types of defect centres is found in each specimen. The presence or absence of nitrogen has long been known to give rise to the distinctive properties of Type I and Type II diamond.The present survey has shown that the form in which the nitrogen is present is significant. In most specimens the nitrogen is present in substitutional, non-paramagnetic platelet form, and these specimens were classified as Type Ia diamonds. A small group of transparent natural diamonds was found to contain dispersed paramagnetic nitrogen. The optical properties of these diamonds are unlike those of other diamond types and have hitherto not been reported. It is proposed that these diamonds be classified as Type lb.Three new systems of E.P.R. lines were found in Type Ib diamond. They are shown to be due to: (i) 13C atoms situated in different positions relative to the substitutional nitrogen, (ii) interaction of the small quadrupole moment of the nitrogen with the electric field gradient, and (iii) the presence of the l5N isotope. Synthetic diamonds are found to be exclusively of the Type Ib variety, whereas natural Type Ib diamond are rare exceptions. This is attributed to the growth history of the specimens. In order to investigate the defect centres associated with nitrogen in diamond, Type Ia and Ib diamond were irradiated with 0.78 MeV electrons. The effects observed were complicated and therefore led to a general investigation of irradiation damage, and the annealing of irradiation damage in diamond. In addition to the G.R.l and U.V. bands induced in all diamond by irradiation damage, another optical absorption feature, the N.D.l band, is found in all Type Ia diamond after irradiation and limited heating. It is suggested that the N.D.l centre arises from the combination of a carbon interstitial, and nitrogen in platelet form, and that the other primary product of irradiation damage, a vacancy, is responsible for both the G.R.l and U.V. bands. The N.D.l centre acts as an acceptor, the G.R.l centre as a donor. In the ionized state G.R.l is inactive in optical absorption; N.D.l is active. Electron transfer by thermal excitation results in the bleaching of G.R.l and the enhancement of N.J.l. Illumination with light in the N.D.l band causes electron transfer in the reverse direction, restoring band strengths to their former condition. A model is proposed which defines the energies within the forbidden gap of the ground and excited states of G.R.l and N.D.l. On heat treatment at temperatures of 500°C and above, the G.R.l band in all diamonds anneals out. The rate of annealing, however, is founa to be dependent on the nitrogen concentration. Thus in Type IIa diamond (which contains no nitrogen) G.R.l anneals very slowly, resulting in the formation of an absorption tail. In Type Ia diamond G.R.l anneals much faster (the actual rate depending on the nitrogen concentration), and two optical absorption bands, 5032A and H2, are formed. It is proposed that the vacancy in diamond becomes mobile at about 500° C, and that the G.R.l band in Type IIa diamond anneals because of the agglomeration of vacancies, which results in the formation of defects responsible for the absorption tail. In Type Ia diamond the nitrogen platelets are ideal sinks for vacancies, because the lattice on either side of a platelet is in compression. G.R.l therefore anneals more rapidly and 5032A centres are formed due to the combination of a vacancy and a nitrogen platelet. The nature of the H2 centre is much more obscure, but a possible explanation is that H2 centres are formed in addition, because the N.D.l centres (nitrogen platelets with embedded interstitials) also succeed in trapping vacancies. Vacancy/interstitial recombinations are prevented since these defects are pinned to different locations in the platelet region. In type Ib diamonds N. D.l centres were found to form at a lower temperature than in Type Ia diamond. It is suggested that the carbon interstitial in diamond is mobile, and combines with Substitutional nitrogen in isolated positions at temperatures below 250°C. In Type Ia specimens, where the nitrogen is segregated in platelets, this process only occurs at about 250°C, when the interstitial has enough kinetic energy to overcome the energy barrier preventing it from combining with nitrogen inside the platelet region where it will relieve strain. Because of the different substitutional nitrogen configuration, the energy levels of N.D.l centres in Type Ib diamond are such that electron transfer by thermal excitation from G.R.l to N.D.l occurs at room temperature. Most of the G.R.l centres are therefore permanently ionized and optically inactive. After heat treatment, a new band called the 6400A band is formed in irradiated Type Ib diamond. It is suggested that 6400A centres are formed by the combination of mobile vacancies with substitutional nitrogen in isolated positions. The 6400A band is therefore analogous to the 5032A band produced in Type Ia diamond. As expected no analogue of the H2 is formed in Type Ib diamond, as both an interstitial and a vacancy cannot co-exist in combination with a single isolated substitutional nitrogen atom.
Keywords: Diamonds -- defects; Electron optics; Solid state physics; Diamonds -- analysis; Electron paramagnetic resonance